2018
DOI: 10.1038/s41598-018-27098-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mesenchymal Stem Cell Differentiation by Nanopatterning of Bulk Metallic Glass

Abstract: Mesenchymal stem cell (MSC) differentiation is regulated by surface modification including texturing, which is applied to materials to enhance tissue integration. Here, we used Pt57.5Cu14.7Ni5.3P22.5 bulk metallic glass (Pt-BMG) with nanopatterned surfaces achieved by thermoplastic forming to influence differentiation of human MSCs. Pt-BMGs are a unique class of amorphous metals with high strength, elasticity, corrosion resistance, and an unusual plastic-like processability. It was found that flat and nanopatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 63 publications
2
40
0
Order By: Relevance
“…hMSCs are involved in numerous treatments in various diseases due notably to their differentiation potential . We focus especially here on the adipogenesis potential for reconstructive medicine to cite only one example.…”
Section: Resultsmentioning
confidence: 99%
“…hMSCs are involved in numerous treatments in various diseases due notably to their differentiation potential . We focus especially here on the adipogenesis potential for reconstructive medicine to cite only one example.…”
Section: Resultsmentioning
confidence: 99%
“…One important property of bone marrow-derived mesenchymal stem cells is to differentiate into different specialized cell types such as osteoblasts and adipocytes. 28,29 Along with the capability to produce growth factors, mesenchymal stem cells need their capability of differentiating into different cell types to boost regeneration of injured tissues, 30 and hence exert their therapeutic role. In order to determine whether labeling our mesenchymal stem cells with IO-MI NPs will affect their differentiation capabilities, we performed osteogenic and adipogenic differentiation experiments for labeled and nonlabeled FGF21 MSCs ( Figure 4A) and mCherry MSCs ( Figure 4B).…”
Section: Influence Of Labeling the Mesenchymal Stem Cells With Nanopamentioning
confidence: 99%
“…Studies have shown that substrates with microstructured or nanostructured surfaces could strongly influence the fate of MSCs . Dalby and his colleagues reported that substrates with deliberately disordered pits in a square arrangement (±50‐nm offset) induced MSCs to differentiate into osteoblasts, while nanotopography with pits arranged in absolute square lattice symmetry retained stem‐cell phenotype and maintained stem‐cell growth of MSCs over 8 weeks .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Studies have shown that substrates with microstructured or nanostructured surfaces could strongly influence the fate of MSCs. [13][14][15] Dalby and his colleagues reported that substrates with deliberately disordered pits in a square arrangement (±50-nm offset) induced MSCs to differentiate into osteoblasts, 16 while nanotopography with pits arranged in absolute square lattice symmetry retained stem-cell phenotype and maintained stem-cell growth of MSCs over 8 weeks. 17 Interestingly, it was found that PHBV electrospun nanofibrous scaffolds loaded with hydroxyapatite nanoparticles could induce spontaneous osteogenic differentiation of bone marrow-derived MSCs in the absence of osteogenic inducing media.…”
Section: Introductionmentioning
confidence: 99%